Evaluasi Tingkat Kebugaran Jasmani Mahasiswa pada Perkuliahan Pendidikan Jasmani IAIN Salatiga - Fatkhur Rozi; Setiorini Rahma Safitri; Amanda Syukriadi (Balai Diklat Keagamaan Semarang, 2021)
The purpose of this study was to evaluate the physical fitness level of IAIN Salatiga students after attending physical education lectures in the Odd Semester 2020/2021. This research method is descriptive quantitative research with a survey approach. The results of this study indicate that the physical fitness level of male students with good categories are 5 people (33.3%), the adequate categories are 9 people (60%), and in the poor category is 1 person (6.7%). There were 25 female students in the good category (25.3%), 72 people in the adequate category (72.7%), and 2 students in the poor category (2%). This research concludes that students of IAIN Salatiga who take physical education lectures generally have a good level of physical fitness (26.4%), while others are in the adequate category (71%) and the poor category (2.6%). The suggestion in this research is that the students of IAIN Salatiga always maintain good physical fitness and for further researchers, they can examine the factors that affect the fitness of the students of IAIN Salatiga.